The Influence of Consumer Perception and Brand Image on Gen Z Consumers' Purchase Decisions for Danone (AQUA) Products After the Peak of the Boycott Issue (A Study of Management Students Of The Faculty of Economics and Business, Makassar State University) - Natsir, Uhud Darmawan; Haswan, Aldika Putra; Riu, Isma Azis; Sahabuddin, Romansyah; Musa, Muh. Ichwan (Entrepreneurship, Management, and Business Research Journal, 2025)
This study aims to analyze the influence of consumer perception and brand image on Gen Z consumers' purchase decisions for Danone (AQUA) products after the peak of the boycott issue, focusing on Management students of the Faculty of Economics and Business, Makassar State University. This study uses a quantitative approach with a survey method using a Likert-scale questionnaire to measure consumer perceptions, brand image, and purchase decisions. The analysis techniques used included validity testing, reliability testing, classical assumption testing, multiple linear regression, and t-tests and F-tests to examine partial and simultaneous effects using SPSS version 25. The results of the study indicate that consumer perceptions of AQUA are in the “high” to “very high” category, so that students continue to sort information and tend to maintain a positive view despite the boycott issue. Brand image is also classified as “high”, indicating that the quality, symbolic value, and consumer experience with AQUA remain good. Purchasing decisions are also in the “high” to “very high” category, indicating that although the boycott issue influences considerations, product quality remains the main reason for choosing AQUA. Regression tests prove that consumer perceptions and brand image have a significant influence, both partially and simultaneously, on purchasing decisions.   Penelitian ini bertujuan untuk menganalisis pengaruh persepsi konsumen dan citra merek terhadap keputusan pembelian produk Danone (AQUA) pada konsumen Generasi Z pasca puncak isu boikot, dengan fokus pada mahasiswa Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Makassar. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei melalui kuesioner berskala Likert untuk mengukur persepsi konsumen, citra merek, dan keputusan pembelian. Teknik analisis yang digunakan meliputi uji validitas, uji reliabilitas, uji asumsi klasik, regresi linear berganda, serta uji t dan uji F untuk melihat pengaruh parsial dan simultan menggunakan program SPSS versi 25. Hasil penelitian menunjukkan bahwa persepsi konsumen terhadap AQUA berada pada kategori “tinggi” hingga “sangat tinggi”, sehingga mahasiswa tetap memilah informasi dan cenderung mempertahankan pandangan positif meskipun ada isu boikot. Citra merek juga tergolong “tinggi”, menandakan bahwa kualitas, nilai simbolik, dan pengalaman konsumen terhadap AQUA tetap baik. Keputusan pembelian pun berada pada kategori “tinggi” hingga “sangat tinggi”, menunjukkan bahwa meskipun isu boikot memengaruhi pertimbangan, kualitas produk tetap menjadi alasan utama dalam memilih AQUA. Uji regresi membuktikan bahwa persepsi konsumen dan citra merek berpengaruh signifikan, baik secara parsial maupun simultan, terhadap keputusan pembelian.